2019
DOI: 10.1177/0042098019832468
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of self-organising communities in a gentrifying city

Abstract: While commonly pitched as potential spaces for the empowerment of marginalised minority groups, self-organised projects such as community gardens are also susceptible to neoliberal discourses and governance mechanisms. While relationships between community gardening and gentrification are now well established, less is known about the grassroots strategies of garden groups in the context of such conditions and the ways in which gentrification changes the community gardening movement itself. This paper combines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Many studies have linked informal urban initiatives to gentrification (Mould, 2014; Pinder, 2008) and have shown that the recruitment of social capital in these initiatives involves both the retreat of the welfare state and the entrenchment of market forces (Mayer, 2003). Thus, they might become instrumental in neoliberal governance, and manifest associated inequalities in the process (van Holstein, 2020). The balance of decided and emergent orders explored in this study might help DIY initiatives to achieve more equitable arrangements through a careful maintenance of certain aspects as comparatively structured and organised and other aspects as open and inclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have linked informal urban initiatives to gentrification (Mould, 2014; Pinder, 2008) and have shown that the recruitment of social capital in these initiatives involves both the retreat of the welfare state and the entrenchment of market forces (Mayer, 2003). Thus, they might become instrumental in neoliberal governance, and manifest associated inequalities in the process (van Holstein, 2020). The balance of decided and emergent orders explored in this study might help DIY initiatives to achieve more equitable arrangements through a careful maintenance of certain aspects as comparatively structured and organised and other aspects as open and inclusive.…”
Section: Discussionmentioning
confidence: 99%
“…These developments can result in a democratic deficit, leading to the empowerment of some actors and constraining the openness that characterises self-organisation (Swyngedouw, 2005). These outcomes sabotage the radicality, counter-hegemonic stance and subversive potential of these initiatives and negatively impact associated grassroots-based self-organisation processes (Bach and McClintock, 2021; Elder and Gerlak, 2019; Hou, 2020; van Holstein, 2020).…”
Section: The Organisation Ofcommunity-driven Urban Initiativesmentioning
confidence: 99%
“…At the community level, provision of agricultural production factors mainly consists of the installation of a certain percentage of green space for planting and construction of production service facilities [ 40 , 41 ]. Small-scale planting sites can be established in combination with green spaces between houses and alongside public facilities [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The focus of the research on community gardens as third places was guided by the literature review on community gardens and third places. When studying community gardens as a case study, there are a multitude of directions one could take including: social justice (Lyons et al, 2013); alternative food movements (Cameron & Wright, 2014); urban revitalisation (Thornton, Lyons & Sharpe, 2018); gentrification (van Holstein, 2019); bio-diversity (Maller & Farahani, 2018); addressing urban food deserts (Lewis, Galloway-Gilliam, Flynn, Nomachi, Keener and Sloane, 2011); food security (Singh-Peterson & Lawrence, 2015); and sustainability (Houston, MacCallum, Steele & Byrne, 2016). This thesis builds on an extensive body of literature on community gardens.…”
Section: Scope Of the Studymentioning
confidence: 99%